Pembuatan Alert Sistem Komputer Kabel dan Nirkabel di UK. Petra - Indra Thamrin; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2017)
The monitoring system is an important component that we need a system datacenter. Problem can be occurred if a datacenter system does not have a monitoring system. It could lead to be a problem for a network administrator to manage and monitor servers in a network.This thesis intends to make a system monitoring with monitoring tools namely Zabbix. Zabbix is a monitoring tools that have user friendly interface, and also can display some information needed to improve work of network administrator. Some features such as Telegram API and SMS API added in Zabbix.By doing so, Zabbix can send notification message to network administrator if trouble happens in network. The result shows by adding Telegram API and SMS API in Zabbix, network administrator can reveal network condition in real time.